REDs is prevalent in young biathletes - a need for awareness among sports medicine practitioners - Løkkevik, I. J.; Rustaden, A. M.; Sudngot-Borgen, C.; Macnaughton, L.; Sundgot-Borgen, J.; Lundberg, H. E.; Mathisen, T. F. (BMJ Open Sport & Exercise Medicine, 2026)
Introduction Relative Energy Deficiency in Sport (REDs) can impair both physical and mental health in athletes. This study investigates REDs symptoms and physical and mental health in three biathlete age cohorts at the start of the season and explores their association with end-of-season competition results.